Experience in Obstructive Hyperthrophic Myocardiopathy Surgery at a National Reference Center - Robles, Víctor (2020)
Objectives: To identify the clinical characteristics, analyze the results and show the efficacy of surgical treatment of hypertrophic obstructive cardiomyopathy (HOC), in a national reference institute. Methods: A descriptive, retrospective, case series of patients with the diagnosis of HOC operated at the National Cardiovascular Institute, was performed between December 2016 and January 2019. We analyzed the postoperative evolution of symptomatology, functional class (FC), left ventricular outflow tract gradient (LVOTG) and mitral regurgitation (MR). Results: Thirteen cases with HOC undergoing extended septal myectomy were evaluated. 31% were women and the average age was 39.6 years. Before surgical treatment, 85% were in functional class (FC) III-IV, 85% of patients had severe MR, the mean septum thickness was 27 mm (range from 19 to 39 mm), and mean LVOTG was 111 mmHg (range from 60 to 150 mmHg). After surgical treatment we found improvement of the functional class (69% in FC I) and the degree of MR (92% with zero or minimal), and reduction of mean LVOTG to 16 mmHg (range from 6 to 35 mmHg). Simultaneous surgery of the mitral valve was performed in 7 patients (54%). Conclusions: Our experience in HOC surgery is good. The treatment of both myocardial and valve components allows reducing LVOTG and correcting MR.